Factors Predicting the Effectiveness of Celebrity Endorsement Advertising: HND Marketing Students Perspective (Global Journal of Management and Business Research, 2020)
Large amount of money is spent in contracting celebrity endorser to promote firms#x2019; brands. The purpose of this study was to reveal factors predicting the effectiveness of celebrity endorsement advertising from HND marketing student#x2019;s perspective. The study utilized quantitative research design, Correlational and descriptive analysis via SPSS. The study collected both primary data via questionnaire and secondary data via literature review. Convenient sampling techniques were used.
Keywords: advertising; celebrity; effectiveness; endorsement